أقسام شركات العقود وأحكامها: دراسة مقارنة بين المذاهب الأربعة - احمدو, عمار (University of Eloued جامعة الوادي, 2023)
يعتبر فقه الشركات من أهم الفقه الذي يُشْكل على المسلم، لتعرضه له في المعاملات، ولتشعب أحكامه، خصوصا من ناحية أقسام الشركات، وما ينبني على ذلك من اختلاف أحكام، فخصصت هذه الدراسة له، وقد توصلت إلى أن الفقهاء قسموا الشركات باعتبارين: باعتبار الصيغة التي وقع بها العقد، ومدى الحرية الممنوحة للشريكين في التصرف، وبهذا الاعتبار قسموا الشركات إلى شركات عنان، ومفاوضة. والاعتبار الثاني باعتبار الشيء المتشارك به، وهو إما أن يكون مالا من الطرفين، وهذه ينظر فيها هل وقعت مفاوضة، أو عنانا، فهي محلّ تحقق القسمين الأولين. والقسم الثاني عند خلوها من المال؛ وعليه إ أن تكون بعمل يقدمه كل من الشريكين، وهي شركة العمل، أو أن تكون ذممهما، وضمانتهما، وهي شركة الوجوه. The jurisprudence of companies is considered to be one of the most challenging jurisprudence issues that face Muslims due to their exposure to it in their transactions, and the complexity of its rulings, especially in terms of corporate divisions, and the different rulings based on that. For the above reasons, this study aims to investigate this issue. The findings revealed that Islamic jurists have divided companies based on two considerations: firstly, they consider the formula in which the contract was signed, and the extent of the freedom granted to the two partners to act. Based on this consideration, the jurists divided the companies into partnership (Anan) and negotiation (Mufawadha) companies. The second consideration is regarding the shared thing, which is either money from the two parties, and this is to be investigated whether a negotiation took place (Mufawadha) or whether it was the second type of partnership (Anan). In addition, the second consideration can be a work provided by each of the two partners, their credits or guarantees.
مقال
Keywords: عقود الشركات؛ ; الأقسام؛ ; المذاهب الأربعة؛ ; دراسة مقارنة؛ ; شركة المفاوضة؛ ; شركة العنان ; Corporate Contracts; sections; The four schools of Islamic jurisprudence; A comparative study; Partnership company (Anan); Negotiation companies (Mufawadha).